Difficulty factors for VR cognitive rehabilitation training – Crossing a virtual road. (October 2019) - Wagner, Sebastian; Joeres, Fabian; Gabele, Mareike; Hansen, Christian; Preim, Bernhard; Saalfeld, Patrick
Highlights: Immersive VR environment for the training of safe road crossing decisions. Relevant Lanes and Traffic Speed have a clear influence on task difficulty. No clear influence could be found for the Gap Size. The Number of Vehicles had almost no effect on the perceived task difficulty. Two neuropsychologists stated that the system is ready for a study on patients. Graphical abstract: Abstract: Patients with cognitive or visual impairments have problems in dealing with complex situations. During the rehabilitation process, it is important to confront the patient with (everyday) tasks that have increasing degrees of difficulty to improve their performance. Immersive virtual reality training offers the potential to create a better transfer to daily life than non-immersive computer training. In cooperation with two neuropsychologists, an immersive virtual environment (VE) was developed in which cognitive training in the form of safe road crossing decisions can be performed. We present the experimental exploration and evaluation of difficulty factors within such a VR-based cognitive rehabilitation program. Four difficulty factors were identified and compared (number of relevant traffic lanes, speed of vehicles, distance between vehicles, and number of vehicles). The combination of these difficulty factors resulted in 36 training scenarios. The impact of the factors on participant performance and subjective perception of scenario difficulty were evaluated with 60 healthy participants to estimate the impact of the four factors to a situation's difficulty level. For the factors Relevant Lanes and Traffic Speed a clear influence on the perceived task difficulty could be determined. No clear influence could be found for the Gap Size . The Number of Vehicles had almost no effect on the perceived task difficulty. Finally, we asked two experienced neuropsychologists about the applicability of our developed system to patients, and they stated that the system is ready for a study on patients.